Global heart warming: kama muta evoked by climate change messages is associated with intentions to mitigate climate change - Seibt, Beate; Zickfeld, Janis H.; Østby, Nora (Frontiers in Psychology, 2023)
Concern about climate change is often rooted in sympathy, compassion, and care for nature, living beings, and future generations. Feeling sympathy for others temporarily forms a bond between them and us: we focus on what we have in common and feel a sense of common destiny. Thus, we temporarily experience communal sharing relationships. A sudden intensification in communal sharing evokes an emotion termed kama muta, which may be felt through tearing up, a warm feeling in the chest, or goosebumps. We conducted four pre-registered studies (n = 1,049) to test the relationship between kama muta and pro-environmental attitudes, intentions, and behavior. In each study, participants first reported their attitudes about climate change. Then, they received climate change-related messages. In Study 1, they saw one of the two moving video clips about environmental concerns. In Study 2, participants listened to a more or less moving version of a story about a typhoon in the Philippines. In Study 3, they listened to a different, also moving version of this story or an unrelated talk. In Study 4, they watched either a factual or a moving video about climate change. Participants then indicated their emotional responses. Finally, they indicated their intentions for climate mitigation actions. In addition, we measured time spent reading about climate-related information (Studies 1, 2, and 4) and donating money (Study 4). Across all studies, we found that feelings of kama muta correlated positively with pro-environmental intentions (r = 0.48 [0.34, 0.62]) and behavior (r = 0.10 [0.0004, 0.20]). However, we did not obtain evidence for an experimental effect of the type of message (moving or neutral) on pro-environmental intentions (d = 0.04 [−0.09, 0.18]), though this relationship was significantly mediated by felt kama muta across Studies 2–4. The relationship was not moderated by prior climate attitudes, which had a main effect on intentions. We also found an indirect effect of condition through kama muta on donation behavior. In sum, our results contribute to the question of whether kama muta evoked by climate-change messages can be a motivating force in efforts at climate-change mitigation.